Bending-resistant torsion-resistant moistureproof control cable
By using composite and crosslinking technology of polyvinyl chloride, ASA resin and other materials in the sheath layer of moisture-proof control cable, the problem of insufficient toughness of the sheath layer is solved, and the bending and torsion resistance of the cable is significantly improved, extending the service life of the cable and reducing the risk of failure.
Patent Information
- Application Number
- CN202510450606.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-04-11
AI Technical Summary
The sheath layer of moisture-proof control cable is not tough enough, which leads to prone to fracture under frequent bending and torsion conditions, affecting the service life of the cable.
The sheathing layer materials including polyvinyl chloride, ASA resin, epoxidized natural rubber, fillers, antioxidants, moisture-proofing agents, plasticizers and crosslinking agents are used. Through the composite and cross-linking of these raw materials, the bending and torsion resistance of the cable is improved.
It significantly improves the toughness and durability of the cable sheath layer, extends the service life of the cable, and maintains good performance under complex operating conditions, reducing system maintenance costs and failure risks.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of control cables, and in particular to a bending-resistant, torsion-resistant and moisture-proof control cable. Background Art
[0002] In many fields such as modern industry, construction and communication, cables are key carriers of power and signal transmission, and their performance is directly related to the stability and reliability of system operation. Moisture-proof control cables are widely used in humid environments and underground laying due to their excellent moisture-proof properties, and are an important part of ensuring the normal operation of various facilities.
[0003] At present, the sheath material of moisture-proof control cables is mostly made of polyvinyl chloride (PVC). Although PVC has certain moisture resistance and processing convenience, there is a strong polar interaction in its molecular chain, and the chain segment movement is limited, resulting in the material being rigid but not tough enough. When faced with frequent bending and torsion conditions, it is difficult for the molecular chain to effectively dissipate energy through orientation, slippage, etc., and it is very easy to break, which seriously affects the service life of the cable.
[0004] Therefore, the problem of poor bending and torsion resistance caused by insufficient toughness of the moisture-proof control cable sheath layer not only limits the application scope of the cable under complex working conditions, but also increases the system maintenance cost and failure risk, which needs to be solved urgently to meet the growing demand for high-performance cables. Summary of the invention
[0005] The invention provides a bending-resistant, torsion-resistant and moisture-proof control cable, which solves the problem of insufficient toughness of a sheath layer of the moisture-proof control cable in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides a bending, torsion and moisture-proof control cable, comprising a cable core and a sheath layer covering the cable core; The sheath layer comprises the following raw materials in parts by weight: 60-80 parts of polyvinyl chloride, 5-10 parts of ASA resin, 8-12 parts of epoxidized natural rubber, 10-15 parts of filler, 1-3 parts of antioxidant, 1-4 parts of moisture-proof agent, 5-8 parts of plasticizer, and 2-4 parts of cross-linking agent; The ASA resin has a melt index of 8-10 g / min at 220° C. and 10 kg.
[0007] The ASA resin in the present invention is a terpolymer composed of acrylonitrile, styrene and acrylic ester.
[0008] As a further technical solution, the antioxidant includes an amine antioxidant and a phosphite antioxidant.
[0009] In the present invention, the antioxidant is selected from the composite system of amine antioxidant and phosphite antioxidant. During the use of the cable sheath layer, the amine antioxidant captures free radicals and the phosphite antioxidant focuses on decomposing hydroperoxides. The two together block the oxidation process, ensuring that the sheath layer of the control cable maintains good performance for a long time in a complex environment, thereby ensuring the stable operation of the cable.
[0010] As a further technical solution, the types of the amine antioxidants include one or more of antioxidant 405, antioxidant 1135, and antioxidant 445.
[0011] As a further technical solution, the types of the phosphite antioxidant include one or both of antioxidant 168 and antioxidant 626.
[0012] As a further technical solution, the moisture-proofing agent includes one of calcium chloride and calcium oxide.
[0013] In the present invention, the moisture-proof agent contains moisture in the raw materials during plastic processing, which may cause processing difficulties, such as bubbles, rough surface, etc. Adding calcium chloride or calcium oxide can remove moisture from the raw materials, improve the processing performance of the plastic, and help obtain a control cable sheath layer with a smooth surface and good performance.
[0014] As a further technical solution, the plasticizer includes one or both of dioctyl phthalate and dibutyl phthalate.
[0015] In the present invention, since the interaction between the molecular chains of polyvinyl chloride is strong, the texture is hard and lacks flexibility, the addition of plasticizer can weaken the interaction between the molecular chains, making it easier to slide and deform, lowering the glass transition temperature, and reducing the risk of cable sheath damage caused by mechanical stress. At the same time, the plasticizer can reduce the viscosity of the polyvinyl chloride melt and improve its fluidity, so that the extrusion molding process of the cable sheath has excellent processability.
[0016] As a further technical solution, the cross-linking agent includes an organic peroxide; for example, it may be one or both of dicumyl peroxide and tert-butyl perbenzoate.
[0017] In the present invention, the cross-linking effect of the cross-linking agent enhances the interaction between polymer chains of components such as polyvinyl chloride. When the cable may be bent or twisted by various external forces, the cross-linked sheath layer can better resist these external forces and extend the service life of the cable. The internal structure of the cross-linked sheath layer is tighter, reducing the penetration channels of small molecules (such as water), which enhances the tolerance of the cable sheath to humid environments. In some high-humidity environments, it can better protect the internal cable core and maintain the normal operation of the cable.
[0018] As a further technical solution, the filler includes polyphenylene sulfide fibers and metal oxides in a mass ratio of 1:3 to 3:1.
[0019] In the present invention, the diameter of the polyphenylene sulfide fiber is 10-20 μm, the length is 0.5-1.5 mm, and the slender shape can form an effective network skeleton structure in the polymer matrix. When the cable is bent or twisted, the fiber can effectively prevent the generation and expansion of cracks inside the sheath layer, ensuring the toughness of the material. The particle size of the metal oxide is controlled in the range of 100-300 nm. Under the nano-size effect, the metal oxide performs well in thermal aging protection and other aspects. The polyphenylene sulfide fiber of a specific size and the metal oxide work synergistically on the cable sheath layer to ensure the stable operation of the cable under complex working conditions.
[0020] As a further technical solution, the metal oxide includes one of zirconium dioxide, titanium dioxide and cerium dioxide.
[0021] As a further technical solution, the polyphenylene sulfide fiber has a diameter of 10-20 μm and a length of 0.5-1.5 mm.
[0022] As a further technical solution, the particle size of the metal oxide is 100~300nm.
[0023] As a further technical solution, the polyphenylene sulfide fiber is calcium carbonate composite polyphenylene sulfide fiber.
[0024] As a further technical solution, the preparation method of the calcium carbonate composite polyphenylene sulfide fiber comprises the following steps: A1, mixing calcium carbonate and coupling agent solution, and drying to obtain pretreated calcium carbonate; A2, preliminarily mixing the pretreated calcium carbonate and polyphenylene sulfide, heating to 275-285° C. for a second mixing to obtain a mixture; A3. Melt-spinning the mixture to obtain calcium carbonate composite polyphenylene sulfide fiber.
[0025] During actual use, cables often generate heat due to the passage of electric current, especially when operating at high load or in a high temperature environment. Ordinary sheath materials may degrade in performance due to overheating, or even cause safety hazards. In the present invention, the calcium carbonate composite polyphenylene sulfide fiber in the filler of the sheath layer of the control cable is prepared by blending and encapsulating calcium carbonate and polyphenylene sulfide and then melt-spinning them. In a high temperature environment, the calcium carbonate in the calcium carbonate composite polyphenylene sulfide fiber can effectively absorb and conduct heat, and suppress the rapid rise in temperature, while polyphenylene sulfide maintains the basic form of the structure by virtue of its own characteristics, thereby improving the heat aging stability of the sheath layer of the control cable, so that the cable can still maintain its structural integrity and physical properties at higher temperatures, thereby ensuring the stable operation of the cable in a high temperature environment and preventing the occurrence of thermal aging, and reducing the occurrence rate of failures caused by overheating.
[0026] At the same time, the calcium carbonate composite polyphenylene sulfide fiber shares the metal oxide in the moisture-proof control cable sheath layer, the metal oxide particles are evenly dispersed in the sheath layer matrix, and the calcium carbonate composite polyphenylene sulfide fiber forms a network structure in the matrix. The two cooperate with each other, the metal oxide particles limit the movement of the calcium carbonate composite polyphenylene sulfide fiber, and the stress between the metal oxide and the calcium carbonate composite polyphenylene sulfide fiber is transmitted to each other, which effectively ensures the heat aging resistance of the moisture-proof control cable sheath layer, so that it can still maintain excellent toughness when used in an overheated environment.
[0027] As a further technical solution, the mass ratio of the calcium carbonate to the coupling agent solution is 1:10-20; The mass ratio of the coupling agent to the solvent in the coupling agent solution is 1:45-55.
[0028] As a further technical solution, the coupling agent includes coupling agent DL-411; and the solvent includes toluene.
[0029] In the present invention, the coupling agent can be a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a zirconate coupling agent or a borate coupling agent; the model of the silane coupling agent can be one or both of KH-302 and KH-303; the model of the titanate coupling agent can be one or both of KR-TT2 and KR-TS; the model of the aluminate coupling agent can be one or both of DL-411 and DL-411D; the model of the zirconate coupling agent can be one or more of Zr-801, Zr-802 and Zr-803; the model of the borate coupling agent can be one or both of LD-100P and ZB-99; the coupling agent is preferably an aluminate coupling agent DL-411.
[0030] As a further technical solution, the raw materials of the calcium carbonate composite polyphenylene sulfide fiber include calcium carbonate and polyphenylene sulfide, and the mass of the calcium carbonate is 3% to 5% of the mass of the polyphenylene sulfide.
[0031] In the melt spinning process, the mass of calcium carbonate in the raw material of calcium carbonate composite polyphenylene sulfide fiber is controlled to 3%~5% of the mass of polyphenylene sulfide, which can improve the rheological properties of the spinning fluid, make the calcium carbonate particles dispersed evenly in the polyphenylene sulfide melt, and adjust the viscosity of the melt to make it more conducive to the spinning process, ensuring that the fiber molding quality is more uniform and stable, and reducing the occurrence of problems such as uneven fiber thickness and internal defects.
[0032] As a further technical solution, in step A1, the rotation speed during mixing is 2000-2500 rpm, and the time is 5-10 min; In step A2, the initial mixing temperature is 25-35°C, the rotation speed is 3000-4000 rpm, and the time is 15-20 min; The second mixing speed is 3000-4000 rpm, and the time is 8-12 min; In step A3, the melt spinning temperature is 315-325° C., and the spinning speed is 450-550 m / min.
[0033] The present invention also provides a method for preparing a bending, torsion, and moisture-proof control cable, which is used to prepare the bending, torsion, and moisture-proof control cable, comprising the following steps: The raw materials of the sheath layer are mixed, extruded and coated on the outside of the cable core, and cross-linked to obtain a bending-resistant, torsion-resistant and moisture-proof control cable.
[0034] The working principle and beneficial effects of the present invention are: In the present invention, ASA resin and epoxidized natural rubber are innovatively introduced into the sheath layer material of the polyvinyl chloride moisture-proof control cable. Among them, the selected ASA resin has specific melting characteristics, and its melting index is in the range of 8-10g / min at 220°C and 10kg. This characteristic makes the ASA resin have excellent processing performance when blended with the PVC matrix. At the same time, the ASA resin and the epoxidized natural rubber work together and can improve the toughness of the control cable sheath layer after being added to the PVC matrix and mixed, meeting the higher requirements for the bending and torsion resistance of the cable. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the following examples and comparative examples, the model of polyvinyl chloride is S1000; ASA resin with a melt index of 8 g / min at 220°C and 10 kg, model number XC230G; ASA resin with a melt index of 10 g / min at 220°C and 10 kg, model XC191; ASA resin with a melt index of 14 g / min at 220°C and 10 kg, model XD535; ASA resin with a melt index of 5 g / min at 220°C and 10 kg, model XC811; The model of epoxidized natural rubber is ENR-50; The model of polyphenylene sulfide is 6165A6 HF2000.
[0037] Example 1 The bending-resistant, torsion-resistant and moisture-proof control cable comprises a cable core and a sheath layer covering the cable core; The sheath layer includes the following raw materials in parts by weight: 60 parts of polyvinyl chloride, 5 parts of ASA resin, 8 parts of epoxidized natural rubber, 10 parts of polyphenylene sulfide fiber (diameter of 10 μm, length of 0.5 mm), 0.5 parts of antioxidant 445, 0.5 parts of antioxidant 168, 1 part of calcium chloride, 5 parts of dioctyl phthalate, and 2 parts of diisopropylbenzene peroxide; the melt index of the ASA resin at 220° C. and 10 kg is 8 g / min; The preparation method of the bending-resistant, torsion-resistant and moisture-proof control cable comprises the following steps: The raw materials of the sheath layer are mixed, extruded and coated on the outside of the cable core, and cross-linked to obtain a bending-resistant, torsion-resistant and moisture-proof control cable.
[0038] Example 2 The bending-resistant, torsion-resistant and moisture-proof control cable comprises a cable core and a sheath layer covering the cable core; The sheath layer includes the following raw materials in parts by weight: 80 parts of polyvinyl chloride, 10 parts of ASA resin, 12 parts of epoxidized natural rubber, 15 parts of zirconium dioxide (particle size is 300 nm), 2 parts of antioxidant 445, 1 part of antioxidant 168, 4 parts of calcium chloride, 4 parts of dioctyl phthalate, 4 parts of dibutyl phthalate, and 4 parts of diisopropylbenzene peroxide; the melt index of the ASA resin at 220° C. and 10 kg is 10 g / min; The preparation method of the bending-resistant, torsion-resistant and moisture-proof control cable comprises the following steps: The raw materials of the sheath layer are mixed, extruded and coated on the outside of the cable core, and cross-linked to obtain a bending-resistant, torsion-resistant and moisture-proof control cable.
[0039] Example 3 The bending-resistant, torsion-resistant and moisture-proof control cable comprises a cable core and a sheath layer covering the cable core; The sheath layer includes the following raw materials in parts by weight: 70 parts of polyvinyl chloride, 8 parts of ASA resin, 10 parts of epoxidized natural rubber, 12 parts of zirconium dioxide (particle size is 100 nm), 1 part of antioxidant 445, 1 part of antioxidant 168, 2 parts of calcium chloride, 6 parts of dioctyl phthalate, and 3 parts of diisopropylbenzene peroxide; the melt index of the ASA resin at 220° C. and 10 kg is 8 g / min; The preparation method of the bending-resistant, torsion-resistant and moisture-proof control cable comprises the following steps: The raw materials of the sheath layer are mixed, extruded and coated on the outside of the cable core, and cross-linked to obtain a bending, torsion-resistant and moisture-proof control cable.
[0040] Example 4 The only difference between this embodiment and embodiment 3 is that the melt index of the ASA resin at 220° C. and 10 kg is 10 g / min.
[0041] Example 5 The only difference between this embodiment and embodiment 3 is that zirconium dioxide is replaced by polyphenylene sulfide fibers, and the polyphenylene sulfide fibers have a diameter of 20 μm and a length of 1.5 mm.
[0042] Example 6 The only difference between this embodiment and embodiment 3 is that one quarter of the mass of zirconium dioxide is replaced by an equal amount of polyphenylene sulfide fibers, and the polyphenylene sulfide fibers have a diameter of 20 μm and a length of 1.5 mm.
[0043] Example 7 The difference between this embodiment and embodiment 6 is that the polyphenylene sulfide fiber is replaced with silica composite polyphenylene sulfide fiber; The preparation method of silica composite polyphenylene sulfide fiber comprises the following steps: A1. The coupling agent DL-411 and toluene are mixed in a mass ratio of 1:45 to obtain a coupling agent solution, silicon dioxide is added to the coupling agent solution, mixed at a rotation speed of 2000 rpm for 10 min, and dried to obtain pretreated silicon dioxide; the mass ratio of silicon dioxide to the coupling agent solution is 1:10; the particle size of silicon dioxide is 100 nm; A2. The pretreated silica and polyphenylene sulfide were mixed at 25° C. and a rotation speed of 3000 rpm for 20 min, heated to 275° C., and mixed at a rotation speed of 3000 rpm for 12 min to obtain a mixture; the mass of the silica was 3% of the mass of the polyphenylene sulfide; A3. The mixture was melted at 315° C. and spun at a speed of 450 m / min to obtain silica composite polyphenylene sulfide fibers with a diameter of 20 μm and a length of 1.5 mm.
[0044] Example 8 The difference between this embodiment and embodiment 6 is that the polyphenylene sulfide fiber is replaced with barium sulfate composite polyphenylene sulfide fiber; The preparation method of barium sulfate composite polyphenylene sulfide fiber comprises the following steps: A1. The coupling agent DL-411 and toluene are mixed in a mass ratio of 1:45 to obtain a coupling agent solution, barium sulfate is added to the coupling agent solution, mixed at a speed of 2000 rpm for 10 min, and dried to obtain pretreated barium sulfate; the mass ratio of barium sulfate to the coupling agent solution is 1:10; the particle size of the barium sulfate is 100 nm; A2. The pretreated barium sulfate and polyphenylene sulfide were mixed at 25° C. and a rotation speed of 3000 rpm for 20 min, heated to 275° C., and mixed at a rotation speed of 3000 rpm for 12 min to obtain a mixture; the mass of the barium sulfate was 3% of the mass of the polyphenylene sulfide; A3. The mixture was melted at 315° C. and spun at a speed of 450 m / min to obtain barium sulfate composite polyphenylene sulfide fibers with a diameter of 20 μm and a length of 1.5 mm.
[0045] Example 9 The difference between this embodiment and embodiment 6 is that the polyphenylene sulfide fiber is replaced with calcium carbonate composite polyphenylene sulfide fiber; The preparation method of calcium carbonate composite polyphenylene sulfide fiber comprises the following steps: A1. Mix the coupling agent DL-411 and toluene in a mass ratio of 1:45 to obtain a coupling agent solution, add calcium carbonate to the coupling agent solution, mix at a speed of 2000 rpm for 10 min, and dry to obtain pretreated calcium carbonate; the mass ratio of calcium carbonate to the coupling agent solution is 1:10; the particle size of the calcium carbonate is 100 nm; A2. The pretreated calcium carbonate and polyphenylene sulfide were mixed at 25° C. and a rotation speed of 3000 rpm for 20 min, heated to 275° C., and mixed at a rotation speed of 3000 rpm for 12 min to obtain a mixture; the mass of the calcium carbonate was 3% of the mass of the polyphenylene sulfide; A3. The mixture was melted at 315° C. and spun at a speed of 450 m / min to obtain calcium carbonate composite polyphenylene sulfide fibers with a diameter of 20 μm and a length of 1.5 mm.
[0046] Example 10 The difference between this embodiment and embodiment 3 is that three quarters of the mass of zirconium dioxide is replaced with an equal amount of calcium carbonate composite polyphenylene sulfide fiber; The preparation method of calcium carbonate composite polyphenylene sulfide fiber comprises the following steps: A1. Mix the coupling agent DL-411 and toluene in a mass ratio of 1:55 to obtain a coupling agent solution, add calcium carbonate to the coupling agent solution, mix at a speed of 2500 rpm for 5 min, and dry to obtain pretreated calcium carbonate; the mass ratio of calcium carbonate to the coupling agent solution is 1:20; the particle size of the calcium carbonate is 300 nm; A2. The pretreated calcium carbonate and polyphenylene sulfide were mixed at 35° C. and a rotation speed of 4000 rpm for 15 min, heated to 285° C., and mixed at a rotation speed of 4000 rpm for 8 min to obtain a mixture; the mass of the calcium carbonate was 5% of the mass of the polyphenylene sulfide; A3. The mixture was melted at 325° C. and spun at a speed of 550 m / min to obtain calcium carbonate composite polyphenylene sulfide fibers with a diameter of 20 μm and a length of 1.5 mm.
[0047] Comparative Example 1 The difference between this comparative example and Example 3 is that no ASA resin is added to the raw materials of the sheath layer, and 18 parts (by weight) of epoxidized natural rubber are added.
[0048] Comparative Example 2 The difference between this comparative example and Example 3 is that no epoxidized natural rubber is added to the raw materials of the sheath layer, and 18 parts (by weight) of ASA resin are added.
[0049] Comparative Example 3 The only difference between this comparative example and Example 3 is that the melt index of the ASA resin at 220° C. and 10 kg is 5 g / min.
[0050] Comparative Example 4 The only difference between this comparative example and Example 3 is that the melt index of the ASA resin at 220° C. and 10 kg is 14 g / min.
[0051] Experimental Example 1 The sheath layers of the bending, torsion and moisture-proof control cables prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively tested for elongation at break according to standard GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", with the specimen type being 1B specimen, the specimen thickness being 1 mm, and the test speed being 50 mm / min. The results are shown in Table 1 below.
[0052] Table 1 Performance test results
[0053] Compared with Comparative Examples 1 to 4, the sheath layer of the bending, torsion-resistant and moisture-proof control cables prepared in Examples 1 to 4 has a higher elongation at break, indicating that after the epoxidized natural rubber is compounded with the ASA resin having a melt index of 8 to 10 g / min at 220°C and 10 kg and added to the polyvinyl chloride matrix, the toughness of the control cable sheath layer is improved, and the cable has excellent bending and torsion resistance.
[0054] Experimental Example 2 The sheath layers of the bending, torsion-resistant and moisture-proof control cables prepared in Example 3 and Examples 5 to 10 were respectively subjected to heat aging at 135° C. for 168 h. The elongation at break of the sheath layer was tested before and after heat aging in accordance with standard GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", the sample type was 1B type sample, the sample thickness was 1 mm, the test speed was 50 mm / min, and the results are shown in Table 2 below.
[0055] Table 2 Performance test results
[0056] Compared with Example 3 and Examples 5 to 8, the sheath layer of the bending-resistant, torsion-resistant and moisture-proof control cable obtained in Examples 9 to 10 has a small change in elongation at break after thermal aging, indicating that the calcium carbonate composite polyphenylene sulfide fiber and the metal oxide work together to improve the heat aging resistance of the sheath layer of the control cable.
[0057] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A bending, torsion and moisture-proof control cable, characterized in that: It comprises a cable core and a sheath layer covering the cable core; The sheath layer comprises the following raw materials in parts by weight: 60-80 parts of polyvinyl chloride, 5-10 parts of ASA resin, 8-12 parts of epoxidized natural rubber, 10-15 parts of filler, 1-3 parts of antioxidant, 1-4 parts of moisture-proof agent, 5-8 parts of plasticizer, and 2-4 parts of cross-linking agent; The ASA resin has a melt index of 8 to 10 g / min at 220° C. and 10 kg; The filler comprises polyphenylene sulfide fiber and metal oxide in a mass ratio of 1:3 to 3:1; The polyphenylene sulfide fiber is calcium carbonate composite polyphenylene sulfide fiber.
2. The bending, torsion and moisture-proof control cable according to claim 1, characterized in that: The antioxidants include amine antioxidants and phosphite antioxidants; The desiccant includes calcium chloride; The plasticizer includes one or both of dioctyl phthalate and dibutyl phthalate; The cross-linking agent includes an organic peroxide.
3. The bending, torsion and moisture-proof control cable according to claim 1, characterized in that: The polyphenylene sulfide fiber has a diameter of 10-20 μm and a length of 0.5-1.5 mm.
4. The bending, torsion and moisture-proof control cable according to claim 1, characterized in that: The particle size of the metal oxide is 100-300 nm.
5. The bending, torsion and moisture-proof control cable according to claim 1, characterized in that: The preparation method of the calcium carbonate composite polyphenylene sulfide fiber comprises the following steps: A1, mixing calcium carbonate and coupling agent solution, and drying to obtain pretreated calcium carbonate; A2, preliminarily mixing the pretreated calcium carbonate and polyphenylene sulfide, heating to 275-285° C. for a second mixing to obtain a mixture; A3. Melt-spinning the mixture to obtain calcium carbonate composite polyphenylene sulfide fiber.
6. The bending, torsion and moisture-proof control cable according to claim 5, characterized in that: The mass ratio of the calcium carbonate to the coupling agent solution is 1:10-20; The mass ratio of the coupling agent to the solvent in the coupling agent solution is 1:45-55.
7. The bending, torsion and moisture-proof control cable according to claim 5, characterized in that: The raw materials of the calcium carbonate composite polyphenylene sulfide fiber include calcium carbonate and polyphenylene sulfide, and the mass of the calcium carbonate is 3% to 5% of the mass of the polyphenylene sulfide.
8. The bending, torsion and moisture-proof control cable according to claim 5, characterized in that: In step A1, the rotation speed during mixing is 2000-2500 rpm, and the time is 5-10 min; In step A2, the initial mixing temperature is 25-35°C, the rotation speed is 3000-4000 rpm, and the time is 15-20 min; The second mixing speed is 3000-4000 rpm, and the time is 8-12 min; In step A3, the melt spinning temperature is 315-325° C., and the spinning speed is 450-550 m / min.
Citation Information
Patent Citations
Polyphenyl thioether / superfine calcium carbonate microparticle complex fiber and preparation method thereof
CN101363144A
Heat-resistant and ageing-resistant cable sheath material
CN106146926A
High-performance modified PVC alloy and preparation method and application thereof
CN118307903A
Vinyl chloride resin thin extrusion molding and coextrusion laminate
JP2014231565A